Rural Assets Administration and Establishment of Village-Owned Enterprises for the Enhancement of Rural Economy - Sara, I Made; Jayawarsa, A. A. Ketut; Saputra, Komang Adi Kurniawan (Jurnal Bina Praja, 2021)
This research aimed to examine the effect of village-owned asset administration and the formation of village-owned enterprises on improving the economy of rural communities. This research was conducted in Bali Province with a population of 636 villages. Furthermore, a sampling technique using proportionate stratified random sampling found 87 samples of the study. With a survey research design using a questionnaire, the data is collected directly by the researcher towards the respondent. The collected data were analyzed using multiple linear regression techniques. This study indicates that the administration of village assets and the formation of village-owned enterprises have a significant positive effect on improving the rural economy. The contribution of the research is to develop policy theory that is used as a basis for research discussion and practical contributions to be used as village observers, village practitioners, and village government as a basis for decision making and village entrepreneurship development for community welfare. The administration of village assets aims to ensure that all village assets under the control of the asset manager are recorded properly. In this research, suggestions for improving regulations governing the management of village assets can be suggested.